2017
DOI: 10.1016/j.schres.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility and clinical benefits of improving facial affect recognition impairments in schizophrenia: Systematic review and meta-analysis

Abstract: Facial affect recognition difficulties in schizophrenia are highly responsive to psychological interventions designed to improve them, and there is early evidence that this may lead to large gains in social functioning for this group - but not symptoms. A large-scale high-quality RCT with longer-term follow-up period is now required to overcome the limitations of the existing evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 57 publications
2
24
0
Order By: Relevance
“…Finally, in the FEP group, correct identification of fear was correlated with better quality of social relationships, with a possible interpretation that patients with a better ability to recognize other people's emotions have better social skills and are more satisfied with their relationships. Although we were not assessing our patients' functionality, these results could be in line with previous studies that show lower levels of social functioning in patients with poorer emotional recognition performance (Bordon, O'Rourke, & Hutton, 2017;Irani, Seligman, Kamath, Kohler, & Gur, 2012;Pinkham et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Finally, in the FEP group, correct identification of fear was correlated with better quality of social relationships, with a possible interpretation that patients with a better ability to recognize other people's emotions have better social skills and are more satisfied with their relationships. Although we were not assessing our patients' functionality, these results could be in line with previous studies that show lower levels of social functioning in patients with poorer emotional recognition performance (Bordon, O'Rourke, & Hutton, 2017;Irani, Seligman, Kamath, Kohler, & Gur, 2012;Pinkham et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…Second, the results also suggest that FER of anger and fear may depend on or contribute to clinical symptoms. Thus, assessment of FER should be included in the clinical assessment and treatment plan from the beginning of the illness, especially since studies have found positive results for treatment directed toward emotional processing (Bordon et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…FAR is among the most researched areas of social cognition in schizophrenia. Systematic reviews of studies investigating psychological interventions targeting FAR have demonstrated that such interventions are efficacious in improving FAR performance and functional status, but not psychotic symptoms [ 57 , 58 ]. For example, a 6-week computerized intervention that included both cognitive training and FAR training was shown to significantly improve FAR and social functioning (assessed using the Personal and Social Performance scale [PSP]) in clinically stable male outpatients with schizophrenia [ 59 ].…”
Section: Core Domains Of Social Cognition In Schizophreniamentioning
confidence: 99%
“…Besides, it suggests that the DOP might be helpful for people presenting schizotypal personality traits since participants in the HS group starting in the DOP condition especially benefit from this procedure when recognising disgusted faces, although this effect was not observed with other negative emotions. A recent systematic review (Bordon et al, 2017) suggests that improving the emotional facial expression recognition of patients with schizophrenia may lead to a large gain in social functioning for this group. However, since participants of the present research do not belong to the clinical population, it would be necessary to replicate these findings in patients in order to be sure of the usefulness of this procedure to improve these impairments in different populations, so future studies should explore this issue.…”
Section: Discussionmentioning
confidence: 99%